Wildlife as insurance against rainfall fluctuations in a semi-arid savanna setting of southeastern zimbabwe - Poshiwa, X.; Groeneveld, R.A.; Heitkönig, I. M.A.; Prins, H.H.T.; van Ierland, E. C. (Tropical conservation science, 2013)
This paper presents modeling approaches for wildlife conservation in a semi-arid savanna setting where there are frequent occurrences of drought. The model was used to test the extent to which wildlife income offers opportunities to reduce fluctuations in income as a result of variations in annual rainfall. For the application of the model the wildlife and agro-pastoral systems of southeastern Zimbabwe were simulated. Results show that wildlife income has the potential to compensate for some of the losses in expected income from livestock during droughts. However, wildlife income becomes second best to irrigated agriculture in stabilizing income in areas that show highly fluctuating rainfall. Possible reasons for this include high costs of exploiting the wildlife resource, and the small fraction of wildlife revenues received by households and communities. In order to search for sustainable solutions in areas such as the southeastern low veld of Zimbabwe, it is also important to be aware that the current human population and livestock densities are far above current sustainable levels. Our results therefore suggest that current and future efforts to conserve biodiversity are doomed to fail if there are no efforts made to decongest areas surrounding parks of high densities of human and herbivore populations, and to let local households earn more revenues from wildlife.